The simulation of low-level equatorial local winds in Peninsular Malaysia during the haze episode of 1997 through the LADM - Mastura Mahmud, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
Weak low level winds in the equatorial region pose a problem in the dispersion and diffusion of local pollutants, particularly, when large-scale vegetation burning causes transboundary haze that lasts for few weeks during which the air quality may deteriorate and cause health problems in the neighbouring countries. This paper investigates the patterns of the low level mesoscale wind flow in Kuala Lumpur in which the patterns of the local equatorial low level wind fields were simulated during the height of the major haze episode of Southeast Asia in September 1997. The backward air trajectories from Kuala Lumpur in Peninsular Malaysia that ended on 17 September 1997 showed that nearly all the wind paths originated from Sumatera at the three pressure height levels of 950, 850 and 700 hPa. The mesoscale wind field patterns that influenced the dispersion of smoke from the burning areas that originated from Sumatera, Indonesia were simulated in this study by utilising the Lagrangian Atmospheric Dispersion Model (LADM). Outputs of the low level wind field patterns generated showed the existence of recirculation of air particles from the diurnal regimes such as the land and sea breezes in addition to the weak prevailing winds across the Kuala Lumpur region during the period when pollution levels were high. The patterns revealed that the weak strength of the local winds did not promote effective dispersion of pollutants advected over the area from transboundary sources a few hundreds of kilometres away